Citrus sinensis Peel Extract Synergistically Enhances the Cytotoxic Effect of Chemotherapeutic Agents on HepG2 Cells - Zufairo, Shofa Khamdanatuz; Rahmawati, Desty Restia; Meiyanto, Edy; Susidarti, Ratna Asmah (Indonesian Society for Cancer Chemoprevention, 2023)
Doxorubicin (DOX) and cisplatin (Cis), non-specific chemotherapeutic agents used for hepatocellular carcinoma (HCC), are frequently combined with synthetic or natural agents to enhance their cytotoxic effects. Citrus sinensis peel extract (CPE) serves as a natural source of flavonoids, including sinensetin (SIN), which has the potential to increase the efficacy of DOX and Cis. This study aimed to observe the effect of CPE and SIN one of CPE compounds, in enhancing liver cancer cell susceptibility to doxorubicin and cisplatin. The assays conducted in this study included a phytochemical analysis of CPE using TLC, cell viability assays against HepG2 cells using MTT assay in both single and combination forms, and cell viability assays on Vero cells. The result confirmed the presence of SIN as one of the compounds in CPE. Both CPE and SIN, when used individually, exhibited moderate cytotoxic effects on HepG2 cells with IC50 of 101.09 μg/mL and 83.13 μM, respectively, while showing no cytotoxic effect on Vero cells. Cis demonstrated significant cytotoxicity against HepG2 cells with an IC50 of 7.86 μM. DOX exerted a strong cytotoxic effect on both HepG2 and Vero cells, with the IC50 of 2.52 μM and 13.98 μM. It was observed that CPE was able to synergistically enhance the cytotoxic effects of DOX, and SIN synergistically increased the cytotoxicity of Cis, particularly against HepG2 cells, with CI<1.0.Keywords: CPE, SIN, Cisplatin, Doxorubicin, HCC.